Team Teaching An Annotated Bibliography. - Marin County Public Schools, Corte Madera, CA.; Marin County Public Schools, Corte Madera, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Team teaching consists of four major types of teams emerging in the public school staffing patterns: (a) interdisciplinary groupings of teachers with diversified specialties; (b) groupings of teachers with instructional aides, paraprofessionals, and volunteers; (c) teams focusing on specific subject matter areas and related curriculum development endeavors; and (d) groupings of teachers and other specialized auxiliary personnel. This annotated bibliography reviews selected literature focusing on the various aspects of team teaching in the public schools. Twenty-eight citations are listed in alphabetical order. (MJM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Educational level discussed: Elementary Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Educational Innovation; Elementary Education; Public School Teachers; Secondary Education; Teacher Education; Teaching Methods; Team Teaching; Reference Materials, Bibliographies